Pelatihan Pemanfaatan Limbah Minyak Jelantah Menjadi Lilin Aromatik - Septi Tri Dinanti; Yudia Gusti Fitiyani; Heli Pera Mistika; Fitri Indah Lestari; Aprianto Aprianto; Alda Julianti; Mahrifatun Khasanah; Tjik Siti Afifa Azzahra; Mona Chairun Nisa; Nabilah Nur Atikah; Lili Utami; Alfiah Thalia Nabila Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
Bankruptcy as a legal remedy for creditors to receive payment from debtors can cause losses for concurrent creditors. The absence of the right to precedence, resulting in concurrent creditors can only receive payment if preferred creditors and separatist creditors have received payment, therefore, it is important to provide legal protection for concurrent creditors in obtaining their right to receive payment. In this research, a normative juridical method will be used through literature study. By using secondary legal sources as well as primary and secondary legal materials relevant to the protection of concurrent creditors in bankruptcy cases. In the research results, it was found that there is an urgency to apply the insolvency test as an effort to protect concurrent creditors from losses to debtors declared bankrupt. Then, it is also important for concurrent creditors to file legal remedies in the event that the debtor is declared bankrupt, but still has the financial ability to pay his debts.